MUTU LAYANAN DAN KEPUASAN MAHASISWA STUDI KASUS DI UNIVERSITAS NEGERI SEMARANG - Rasdi Ekosiswoyo (Jurnal Penelitian Pendidikan, 2015)
Students as the main external consumer groups should benefit, as well as the perpetrators of the formation process of the added value in the implementation of high-quality academic activities in educational institutions (Salis, 2002). Accordingly, Unnes in preparing the 2010-2014 Strategic Plan has set a vision Become conservation university, international, healthy, superior, and prosperous by 2020. To accomplish this purpose, the entire academic community Semarang State University has the same commitment to always improve the quality of management in providing services to stakeholders, both with regard to academic services, and non-academic. That is why, in order to strengthen the loyalty of stakeholders, especially students, the university should be able to provide optimal service. However, the issue is whether the Semarang State University is able to provide services as expected by stakeholders, so that they feel satisfied with the service received? This study was designed as a research survey explanatory phenomena (explanatory research) and includes research is correlational. The population in this study were all students Unnes which totaled 24,650. The study sample consisted of 400 students from FIP, FBS, Faculty and FT. Data was analyzed using descriptive analysis and Structural Equation Medoling (SEM). The results showed that the tangible, reputation, cooperation and support, reliability, and responsiveness has a positive influence on the quality of service in Unnes. Quality of service in Unnes also affect student satisfaction.